Faktor-Faktor yang Mempengaruhi Kunjungan Ibu Membawa Balita Ke Posyandu di Wilayah Kerja Puskesmas Tanah Abang Kabupaten Pali Tahun 2022 - Rini Herdiani; Sunirah S; Ria Wulandari (Madani: Jurnal Ilmiah Multidisiplin, 2023)
Posyandu is a community-based health effort managed and organized from, by, for and with the community in implementing it to empower the community and provide convenience in obtaining basic health services. Utilization of health services is closely related to service quality. Limited funds for fostering and developing the posyandu program, the visits to the posyandu have decreased. in the working area of the Tanah Abang Health Center there are 3 posyandu namely Posyandu Brothers visited 153 babies and toddlers, Posyandu Seruni gan 160 babies and toddlers, Posyandu Harapan 136 babies. General Objective: to find out the factors associated with visiting mothers carrying toddlers to posyandu in the working area of the Tanah Abang Community Health Center in PALI Regency in 2022. This type of research is an analytic survey with a cross sectional approach method. The population is all mothers who have toddlers and live in the working area of the Tanah Abang Public Health Center, PALI Regency in 2023. The population is all mothers who have toddlers and live in the working area of the Balai Agung Health Center, Musi Banyuasin Regency, totaling 459 samples 83 people taking the sample using the Accidental Sampling. Data processing: Editing, Coding, Entry Cleaning. Univariate and bivariate data analysis. Research Results There is a relationship between knowledge (p value. 0.000), occupation (p value, 0.006) and distance from home to Posyandu (p value, 0.010) with visits by mothers who bring toddlers to the Tanah Abang Health Center work area in 2022. The conclusion is that all independent variables are related meaningful with the dependent variable. Suggestions to increase knowledge with counseling, reactivate existing posyandu in the work area of the Balai Agung Health Center improve and develop programs that can attract mothers to be attracted to Posyandu